Katerina Gardikas, Landscapes of Disease: Malaria in Modern Greece, Βουδαπέστη, Νέα Υόρκη, Central European University Press, 2018 - ΚΑΡΑΜΑΝΩΛΑΚΗΣ, ΒΑΓΓΕΛΗΣ (Μνήμων, 2024)
ΔΕΝ ΔΙΑΤΙΘΕΤΑΙ ΠΕΡΙΛΗΨΗ ΣΤΑ ΕΛΛΗΝΙΚΑ.